Growth, leaf gas exchange and biochemical changes of oil palm (Elaeis guineensis Jacq.) seedlings as affected by iron oxide nanoparticles - Izad, Ayu Azera (2021)
Iron oxide nanoparticles (Fe3O4 NPs) has a great potential to boost up plant growth. However, depending on the size, concentration and the plant type used, controversial results have been obtained. Therefore, their fate in the plant body should be investigated to lower the negative impacts and raising the beneficial impacts of the Fe3O4 NPs utilization on oil palm, major crop cultivated in Malaysia. Thus, the objectives of this study are 1) to investigate the impact of different Fe3O4 NPs concentrations i.e. (0, 800, 1600 and 2400 mg/L) on the growth, leaf gas exchange and biochemical changes of 3- months old oil palm seedlings and; 2) to study the physiological adaptation (growth, leaf gas exchange and biochemical properties) and uptake of Fe3O4 NPs by the 3-months old oil palm seedlings when exposed to low Fe3O4 NPs concentrations, i.e. (0, 200, 400 and 600 mg/L). Both experiments were arranged in a randomized complete block design (RCBD) and replicated three times. The first experiment revealed that the oil palm seedlings unable to tolerate even the lowest concentration of Fe3O4 NPs (800 mg/L). The plant growth was not significantly affected by Fe3O4 NPs, but it significantly (p ≤ 0.05) reduced the SPAD chlorophyll value and the leaf total stomata density as compared to the control. Besides, the net photosynthesis is significantly reduced due to damage of photosynthetic apparatus of Fe3O4 NPs-stressed seedlings, in comparison to control. Moreover, the production of malondialdehyde (MDA) is positively correlated with the total volume of phenolics and total flavonoids. This observation indicates that an increase in MDA might be responsible for the up-regulation of the secondary metabolites production under high Fe3O4 NPs concentration application. Meanwhile, in the second experiment, the long-term exposure of low Fe3O4 NPs concentration application significantly reduced the plant height, total biomass, basal diameter, leaf number, total leaf area, and relative growth rate. Leaf gas exchange and chlorophyll fluorescence characteristics of treated seedlings decreased under high Fe3O4 NPs application, compared to the control. Electrolyte leakage (EL) and leaf respiration rate were gradually increased as the Fe3O4 NPs application elevated up to 600 mg/L. Proline, total phenolics, and iron content were significantly increased with Fe3O4 NPs application. The increasing magnetic signal of electron spin resonance (ESR) spectra confirmed the existence of Fe3O4 NPs in root cells of the treatment plants. In conclusion, the uptake of Fe3O4 NPs at 200 to 2400 mg/L concentration dramatically reduced the oil palm seedlings growth as well as photosynthesis efficiency and production of secondary metabolites were elevated as physiological adaptation responses of oil palm seedlings to withstand the impact of Fe3O4 NPs application.